Enhancing phylloquinone levels using ultraviolet-A radiation in indoor farming. - Yuyao Kong; Krishna Nemali (PLoS ONE)
Phylloquinone (Phyllo) or vitamin K1 is mostly available in plant-based foods such as spinach and lettuce. Because Phyllo absorption in the human gut is low, foods with significantly high levels of Phyllo can aid in maintaining adequate vitamin K levels when consumed. We conducted two experiments, i.e., monochromatic and broadband, to understand the effects of light quality on enhancing Phyllo levels in lettuce. Both experiments used green romaine lettuce and a customized indoor growth system with light emitting diode (LED) lights. We measured fresh weight (FW), dry weight, leaf area, leaf number, and Phyllo levels in both experiments. Photosynthesis (A)- photon flux density (PPFD) response curves were measured in the second experiment. In the first experiment, plants were grown under six monochromatic light treatments viz., ultraviolet (UV389), blue (B450), green (G521), red (R632), hyper-red (R662), and far-red (FR733) during the entire growth period. Phyllo level was higher in UV389 and not different among other treatments. Vegetative growth parameters trended in the order of R632 > R662/G521 > B450 > UV389 > FR733. These results suggested that UV389 can increase Phyllo levels but its addition can have a negative effect on vegetative growth. In the second experiment, plants were grown under two treatments viz., UV389 substituted in the broadband light (40% of total light) during the stationary growth stage (UVsub) and control (broadband light without substitution). Results indicated that FW was lower by 24% but Phyllo level increased by approximately 175% in the UVsub treatment compared to control. These results suggest that UV389 provided during the stationary growth phase can enhance Phyllo, however, further lowering the percentage of UV389 may be required to minimize the negative effect on vegetative growth. Analysis of A-PPFD curves indicated lower operating photosynthesis (AOP) and light use efficiency (LUE) in the UVsub compared to control. Analysis indicated that UV-A light provided during the stationary growth stage contributed little to AOP. This suggests that increased Phyllo levels from UV-A exposure did not enhance A but likely provided photoprotection by channeling excess excitation energy through alternate pathways.